2006
DOI: 10.1111/j.1440-1754.2006.00916.x
|View full text |Cite
|
Sign up to set email alerts
|

Use of the Internet by parents of paediatric patients

Abstract: A large number of patients use the Internet to find information that influences their attitudes to health care. The services of a medical informatics professional would likely benefit both patients and doctors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

10
172
2
4

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 153 publications
(188 citation statements)
references
References 22 publications
10
172
2
4
Order By: Relevance
“…8 Trustworthiness and utility of the Internet are concerns in health care technology. 13,40 Studies have recognized that information found on the Internet can be inaccurate, 3 difficult to understand, 3,40 and even useless. 35,37 Interestingly, as early as 2001, hydrocephalus was recognized as having the highest-quality online information among all neurosurgery topics.…”
Section: Technology and Internet Usementioning
confidence: 99%
See 2 more Smart Citations
“…8 Trustworthiness and utility of the Internet are concerns in health care technology. 13,40 Studies have recognized that information found on the Internet can be inaccurate, 3 difficult to understand, 3,40 and even useless. 35,37 Interestingly, as early as 2001, hydrocephalus was recognized as having the highest-quality online information among all neurosurgery topics.…”
Section: Technology and Internet Usementioning
confidence: 99%
“…41 Internet research by caregivers about their child's condition shapes their interactions with physicians. 40 Often, caregivers do not disclose their Internet searches to their physicians. 2,38 While physicians are the preferred source of information, 9,13,22,35,40 in reality, caregivers turn to the Internet for answers first, especially for rare and chronic conditions.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…[5][6][7] Caregivers are searching the Internet for answers to questions about their child' s health, often before seeking medical care. 5,[8][9][10][11][12] Social media platforms provide another portal for asking questions and rapidly sharing information about health. 13 Still, given the ubiquity of online information, the variety of health resources has a range of accuracy and reliability.…”
mentioning
confidence: 99%
“…The importance of the concept of 'quality' for parents when sourcing information is of essence if they are to make well informed decisions about their child's care *9, 18, 26-28] Parents look to healthcare professionals for advice and guidance and prefer sources of information that are recommended by their paediatrician or nurse in order to improve knowledge, awareness and inform decision making [8, 9,11,13,14,22,29]. Healthcare professionals therefore have a responsibility to direct or 'prescribe' internet sources that are of high quality and relevant, and that this may be done as part of the consultation process [11,12,15,18,23,30].…”
Section: Information Needs Of Parentsmentioning
confidence: 99%